The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d1ce00245g
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient fluorescent chemosensor for nitro antibiotic detection based on luminescent coordination polymers with 2,6-di(4-carboxyphenyl)pyrazine

Abstract: As a hot-spot issue of global concern, antibiotics' overuse poses a significant threat to the eco-environment and human health. Here, three isostructural coordination polymers with the formula {[M(DCPP)(H2O)]∙(DMF)}n [M =...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…It is worth mentioning that JLU-MOF109 exhibits a similar structure to [Zn(DCPP) (H 2 O)]• (DMF). 52 The experimental PXRD pattern of JLU-MOF109 can match well with the simulated one, which indicates the phase purity of the as-synthesized product (Figure S2).…”
Section: ■ Introductionsupporting
confidence: 66%
“…It is worth mentioning that JLU-MOF109 exhibits a similar structure to [Zn(DCPP) (H 2 O)]• (DMF). 52 The experimental PXRD pattern of JLU-MOF109 can match well with the simulated one, which indicates the phase purity of the as-synthesized product (Figure S2).…”
Section: ■ Introductionsupporting
confidence: 66%
“…Sun et al reported three CPs for the detection of nitro antibiotics through the fluorescence quenching effect. 21 Fu et al synthesized two CPs that can selectively identify levofloxacin (LVX) with high sensitivity. 22 Zhou et al demonstrated that a robust zirconium-based MOF can serve as a sensor to detect tetracycline (TC) in water.…”
Section: Introductionmentioning
confidence: 99%
“…The large amount of sewage discharged from livestock farms, hospitals and antibiotic production plants not only affects water quality, but also produces more resistant bacteria, which indirectly affects human health. [23,46] We selected nine of the most commonly used antibiotics to explore the potential application of complexes 1 and 2 in the rapid and effective detection of antibiotics. The molecular formulas of the nine selected antibiotics list in Figure 8.…”
Section: Nitrofuran Antibiotic Recognition Propertiesmentioning
confidence: 99%
“…[15][16][17][18][19][20] The hybrid properties endowed by the metal and ligand also make it a promising candidate as fluorescence sensors to detect specific species. [21][22][23][24] In the past several years, our research group has been working on bifunctional anionic units as building blocks to construct new complexes with fascinating structures and intriguing properties. [25][26][27][28] At present, in the exploration of phosphonate complexes, some bifunctional or multifunctional ligands such as aminophosphonates or phosphonocarboxylates have been adopted due to their versatile coordination ability.…”
Section: Introductionmentioning
confidence: 99%